Pyrolysis of sunflower seed hulls for obtaining bio-oils - Casoni, Andrés Iván (2014)
Bio-oils from pyrolysis of as received sunflower seed hulls (SSH), hulls previously washed with acid (SSHA) and hulls submitted to a mushroom enzymatic attack (BSSH) were analyzed. The concentration of lignin, hemicellulose and cellulose varied with the pre-treatment. The liquid corresponding to SSH presented a relatively high concentration of acetic acid and a high instability to storage. The bio-oil from SSHA showed a high concentration of furfural and an appreciable amount of levoglucosenone. Lignin was degraded upon enzymatic activity, for this reason BSSH led to the highest yield of bio-oil, with relative high concentration of acetic acid and stability to storage.